The impact of global value chains participation on the current account balance – an empirical study on a sample of economies during the period 2000-2015 - Yahoubi, Mohammed (Dirassat Journal Economic Issue, 2022)
The main goal of this research is to determine the direction and the strength of the impact of global value chains participation (GVCP) on the current account balance. This econometric relation between the two variables has been studied through the application on the five largest advanced economies and the five largest emerging economies in terms of GDP at current prices for the year 2015, in addition to the Algerian economy, using Panel data models with annual observations during the period 2000-2015. After the empirical study we resulted that the pooled model is the best model for the relation’s interpretation between the two variables, where it gives us a result that a high level of GVCs participation contribute positively in the amelioration of the current account position with more than 76% of determination degree. In addition, the estimation results show that the relationship between the two variables becomes negative after the global financial crisis 2008 in the major advanced economies studied, while this relation remained positive for the emergent economies and the Algerian economy before and after the global financial crisis.